Advances in broadband passive optical networking technologies. - Effenberger, F.J.
Several new technological advancements have extended the capabilities of the basic broadband passive optical network (B-PON) described in the ITU-T standard G.983.1. This article describes three of these new technologies: wavelength division multiplexing (WDM), dynamic bandwidth assignment, and survivable networking. These additions to the B-PON family of solutions increase its utility by increasing its raw capacity, its efficiency, and its reliability, respectively. A description is also given of the next wave of innovations that will further extend the B-PON
Keywords: B-PON.; ITU-T standard G.983.1.; WDM; Broadband passive optical network; Dynamic bandwidth assignment; Network capacity; Network efficiency; Network reliability; Survivable networking; Wavelength division multiplexing